Eficácia de uma intervenção fisioterapeutica na qualidade de vida, propriocepção, sensibilidade e mobilidade de idosos diabéticos institucionalizados - Souza, Cibele Cardenaz de (2015)
Introduction: With the increasing life expectancy and the growth of the elderly population, the chronic degenerative diseases develop more frequently. Diabetes mellitus (DM) is one of these diseases, every day more common in this population, which represents a worldwide major public health problem. Individuals who suffer from DM are predisposed to develop neuropathies, reduced proprioception and sensitivity, which can be diagnosed by the detection of higher pressure points and diminished sensitivity in the feet, thus assisting in the prevention of the diabetic foot and its most severe consequences, such as amputation and death. Another very common situation with the elderly population growth is the increasing number of long-term care facilities for the elderly (LTCFE), who, in general, arrive in these facilities when they are older, more fragile, with compromised functional autonomy and independence, as well as presenting various comorbidities, among them the DM is one of the most prevalent. It is, therefore, important to develop therapeutic strategies to improve proprioception and sensitivity of the lower limbs (LL) of elderly diabetics to prevent the diabetic foot and its consequences. Objectives: This study aimed to assess whether a physical therapy program would bring changes in the quality of life, functional mobility, proprioception, tactile and pain sensitivity in the LL of elderly diabetics residing in LTCFE. Methods: In this randomized clinical trial 43 elderly with DM were evaluated. They resided in five LTCFE in the city of Porto Alegre and its metropolitan region. All of them were evaluated before and after a physical therapy intervention [sociodemographic data; assessment of quality of life (SF-36); plantar sensitivity (Semmes Weinstein esthesiometer); functional mobility (Timed Up and Go Test - TUG); proprioception assessment (baropodometry platform)]. After the initial assessment, the elderly were divided into two groups: control (CG; n = 22; 11 women) and intervention (IG, n = 21; 16 women). For nine weeks, the IG undertook a proprioception, sensitivity and gait training, while the CG maintained its usual routine. Results: After the intervention, the IG showed significant improvement (p <0.05) in SF-36 General Score and in the General Health dominium and they also presented significantly higher scores than the CG elderly in terms of the Functional Capacity and Emotional Aspects dominions as well as in the General Score. The results also pointed to the significant reduction in IG’s right foot contact surface, indicative of better distribution of plantar pressure and static balance. Significant differences were not detected in the functional mobility measured by TUG in either group. The control group showed no significant change in any of the measured aspects, except for the increase in the right foot pressure, indicative of an increased risk for the development of plantar ulcers. Conclusion: Based on these results, it can be concluded that the proposed protocol applied to elderly diabetics was effective in improving quality of life and probably in maintaining sensitivity, proprioception, functional mobility and balance.